PhcA and PhcR Regulate Ralsolamycin Biosynthesis Oppositely in Ralstonia solanacearum - Li, Peng; Cao, Xiulan; Zhang, Liwen; Lv, Mingfa; Zhang, Lian-Hui (Frontiers in Plant Science, 2022)
Ralsolamycin, one of secondary metabolites in Ralstonia solanacearum, is known to be involved in crosstalk between R. solanacearum and fungi. Ralsolamycin formation is catalyzed by two hybrid synthetases of RmyA (non-ribosomal peptide synthetase) and RmyB (polyketide synthase). A methyltransferase PhcB catalyzes formation of 3-OH MAME or 3-OH PAME, signals for the quorum sensing (QS) in R. solanacearum, while PhcB positively modulates ralsolamycin biosynthesis. A two-component system of PhcS and PhcR can response these QS signals and activate phcA expression. Here, we experimentally demonstrated that deletion of phcA (ΔphcA) substantially impaired the ralsolamycin production and expression of rmyA and rmyB in R. solanacearum strain EP1, and failed to induce chlamydospore formation of plant fungal pathogen Fusarium oxysporum f. cubense (strain FOC4). However, deletion of phcR significantly increased ralsolamycin production and expression of rmyA and rmyB, and phcR mutants exhibited enhanced ability to induce chlamydospore formation of FOC4. Results of the electrophoretic mobility shift assay (EMSA) suggested that both PhcA and PhcR bind to promoter of rmy operon. Taken together, these results demonstrated that both PhcA and PhcR bind to promoter of rmy operon, but regulate ralsolamycin biosynthesis in an opposite way. It could extend our knowledge on the sophisticated regulatory networks of ralsolamycin biosynthesis in R. solanacearum.